An investigation into the reading harits of some Indian high school pupils on the east rand - Jaga, J (My University, 2015)
Previously, Education in South Africa was divided on a Provincial Level, and although different race groups were taught separately, pupils of each race group wrote the same public examination. However, over the years, legislation had been effected and each race group eas expected to follow . different syllabi and write a separate pub.licexamination at